Metadata quality in learning object repositories: a case study. Issue 1 (28th January 2014) - Palavitsinis, Nikolaos; Manouselis, Nikos; Sanchez-Alonso, Salvador
Abstract : Purpose: – This paper aims to address the issue of poor quality of metadata records describing educational content in Learning Object Repositories (LORs). Through this, it aims to improve the discoverability of learning objects in such LORs through a structured process that supports metadata creation. Design/methodology/approach: – This paper presents a proposed metadata quality assessment certification process for LORs. The process was designed as a generic approach that may be customized to fit various application domains. Findings: – Initial results from the application of the process in the context of a specific LOR report an improvement of the quality of about 11, 000 metadata records. More specifically, metadata completeness for all metadata elements used in the repository under examination was significantly improved from 30 percent to 85 percent. Research limitations/implications: – The main limitation of the findings is that they come from the application of the proposed process on a relatively small repository, which does not allow safe generalizations without further experimental study in bigger ones where resources and requirements scale up. Practical implications: – This paper addresses implications for the development of a repository in the educational domain, identifying issues related to the metadata application profile, the support to domain experts and the mechanisms that may be put in place to support metadata creation. Originality/value: – The value and also the originality of the approach presented lies within the fact the proposed approach quantifies issues related to metadata creation and management by studying actions and perceptions of stakeholders who are involved in the repository lifecycle.